Pengendalian Jamur Ganoderma dengan Metode Perbanyakan Jamur Trichoderma pada Pembibitan Kelapa Sawit di PT PP London Sumatra Bah Lias Research Station - Utami, Mutiara Alya; Nasution, Rizki Amelia; Mawaddah, Fitri Asyiatun; Aulia, Rahma (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Ganoderma sp. usually attack from the root or base of the trunk on the tree whether the tree is alive or dead. There are also other species of Ganoderma whose pileus attaches directly to the tree. Ganoderma whose growth medium is in wood/trees, Ganoderma belongs to "lignicolous" mushrooms. Ganoderma sp. cause rot at the base of the stem (BPB) in oil palm or other productive crops such as rubber, coconut and tea. The tools used in this activity are digital scales, beakers, measuring cups, ovens, LAF, petri dishes, ose needles, hotplates, Bunsen, aluminum foil, autoclaves, knives, heat-resistant plastic or polypropylene, wool thread, gauze plugs, paralon, newspaper, rubber. these activities are potato extract, sugar, agar powder, aquadest, RWB, corn and fine bran. Potato extract 200 gr, sugar 10 gr, agar powder 12 gr. dissolved in 1000 ml of distilled water, the inoculum rubber wood was cut to a size of 6 cm x 6 cm x 6 cm and processed for 7 hours. Then mix the Trichoderma in the soil media. After that, imprisonment was carried out in bags of oil palm in polybags and a high proportion of deaths from oil palm seedlings up to 12 months of age. Trichoderma which acts as an antagonist microbe can suppress the growth of pathogens. By propagating the Trichoderma fungus, which is one of the ways to use biological agents to control 18 plant pests and diseases and can reduce the proportion of deaths in oil palm nurseries. Propagation of Trichoderma fungus on a nursery scale is used as pest and disease control, especially Ganoderma fungus which is currently still a pathogen in oil palm growth. By propagating Trichoderma fungus also cannot rule out the possibility of Ganoderma fungus growing. Keywords: Ganoderma, Trichoderma and Propagation